2020
DOI: 10.1016/j.virusres.2020.198107
|View full text |Cite
|
Sign up to set email alerts
|

A temperature-dependent phenology model for the greenhouse whitefly Trialeurodes vaporariorum (Hemiptera: Aleyrodidae)

Abstract: Highlights Development, mortality and reproduction of T. vaporariorum were studied at constant temperatures ranging from 10 to 32 °C. Nonlinear equations were fitted to the data and a temperature-driven process-based phenology/population growth model for the vector pest established. After adjustment, the model gave good predictions when compared with observed life tables and published data. The model ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 40 publications
1
10
0
1
Order By: Relevance
“…4). Gammara's (et al, 2020) investigation demonstrated that optimal temperature for whitefly development is 22-24 °C. Typical wavelength of HPS lamps (Fig.…”
Section: Resultsmentioning
confidence: 97%
“…4). Gammara's (et al, 2020) investigation demonstrated that optimal temperature for whitefly development is 22-24 °C. Typical wavelength of HPS lamps (Fig.…”
Section: Resultsmentioning
confidence: 97%
“…While this comparison is useful, we caution against over-interpretation due to differences between the studies such as duration of monitoring and size of sampling plots. Turning to insects, we lack other studies focused specifically on phenological skewness in other insect groups, but individual abundance time-series indicate that right-skewness may also be found in univoltine butterflies (Dennis et al, 2017; Scott et al, 1987; Zonneveld, 1991), flies (Haab et al, 2019; Judd et al, 1991), and hemipterans (Gamarra et al, 2020; Ma et al, 2008). Comparisons with multi-voltine species in areas with longer growing seasons are difficult, and further research is needed to compare uni- and multi-modal phenological distributions, especially as climate change creates opportunities for additional generations in some insects (Dyck et al, 2015; Hodgson et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…While this comparison is useful, we caution against over-interpretation due to differences between the studies such as duration of monitoring and size of sampling plots. Turning to insects, we lack other studies focused specifically on phenological skewness in other insect groups, but individual abundance time-series indicate that right-skewness may also be found in univoltine butterflies (Dennis et al, 2017;Scott et al, 1987;Zonneveld, 1991), flies (Haab et al, 2019;Judd et al, 1991), and hemipterans (Gamarra et al, 2020;Ma et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Monitoring, as a second tactic, was taking place alongside during the experiment. Detecting climatic factors was very essential for most of the phytophagous species such as spider mites (Praslicka and Huszár, 2004; White and Liburd, 2005; Zou et al ., 2018), whiteflies (Jha and Kumar, 2017; Khan, 2019; Gamarra et al ., 2020; Chandi et al ., 2021), thrips (McDonald et al ., 1998; Bergant et al ., 2005; Cao et al ., 2018; Garrick and Liburd, 2018), also for predacious mite (Tixier, 2018; Urbaneja-Bernat and Jaques, 2022), as in the current study. As well, for predatory insect (Schuldiner-Harpaz and Coll, 2013), or spider (Blamires and Sellers, 2019; Napiórkowska et al ., 2021) species, and even for the stored product and public health pests (Beckett, 2011; Mahakittikun et al ., 2011) life table parameters, population dynamics, and behaviours which affected due to climate changes.…”
Section: Discussionmentioning
confidence: 99%